La fábula clásica y Horacio en Augusto Monterroso: "proprie communia dicere" - Miralles Maldonado, José C. (Cuadernos de Filología Clásica. Estudios Latinos, 2003)
This paper analyzes the concept of imitation and the use of classical sources in the works of Augusto Monterroso (1921-2003), paying special attention to his fables. Through the analysis of some passages the author concludes that, among many other influences, the Roman poet Horace stands out as a primary source for Monterroso’s work.